Predicting Biochemical Disease-Free Survival after Prostate Stereotactic Body Radiotherapy: Risk-Stratification and Patterns of Failure - Katz, Alan; Formenti, Silvia C.; Kang, Josephine (Frontiers in Oncology, 2016)
Background and Purpose: To determine appropriate risk-stratification factors for prostate cancer patients undergoing stereotactic body radiotherapy (SBRT). Method and Materials: Between 2006-2010, 515 patients with organ-confined prostate cancer were treated with a regimen of 5-fraction SBRT to dose of 35-36.25 Gy. By NCCN criteria, 324 patients were low-risk, 153 were intermediate-risk and 38 were high-risk. Patients were defined as unfavorable intermediate-risk if Gleason 4+3=7 or >1 intermediate risk factors (cT2b-c, PSA 10-20, Gleason 3+4=7). Cox regression analysis was used to determine risk factors significantly associated biochemical failure, and patterns of failure analyzed. Results: With median follow up of 84 months, the 8-year disease free survival was 93.6, 84.3 and 65.0% for low, intermediate and high-risk group patients, respectively. Based on the above define tion 106 favorable intermediate-risk patients had excellent outcomes, with no significant difference compared to low-risk patients (7-y DFS 95.2 vs 93.2%, respectively). The 47 unfavorable intermediate-risk patients had worse outcomes, similar to high-risk patients (7-y DFS 68.2 vs 65.0%, respectively). Gleason score was the only significant factor associated with biochemical failure on multivariate analysis (p=0.0003). Conclusion: Patients with favorable intermediate-risk disease have excellent outcomes, comparable to low-risk patients. Patients with unfavorable intermediate-risk disease have significantly worse outcomes after SBRT, and should be considered for clinical trials or treatment intensification.